Health needs of accompanied refugee and asylum‐seeking children in a UK specialist clinic. (5th April 2021) - Harkensee, Christian; Andrew, Rachel
Abstract: Aim: To identify health needs and healthcare access barriers of accompanied refugee and asylum‐seeking (RAS) children in the North East of England, and pilot a new service model to address these. Methods: Mixed‐methods study (retrospective analysis of routinely collected service data, qualitative data from focus groups) of children who attended a hospital‐based specialist clinic. Results: Over two years, 80 children were referred to this service. Most frequent diagnoses (total n = 104) were anaemia ( n = 17), neurodevelopmental ( n = 12), respiratory ( n = 12) and mental health ( n = 9) conditions. Mild–moderate stunting (23%), overweight and obesity (41%), stunting with obesity (9%) and micronutrient deficiencies (vitamin D (66%), vitamin A (40%) and manifest (14%) or latent (25%) iron deficiency anaemia) were highly prevalent. 62% of children had experienced psychological trauma, and 39% had abnormal results in psychosocial wellbeing screening. 21% of children required secondary or tertiary care, 8% mental health referrals, and 47% were followed up in this specialist clinic. Focus groups with families and the community report unaddressed health needs and substantial barriers of access to health care. Conclusion: Refugee and asylum‐seeking children have substantial health needs and healthcare access barriers that are not routinely addressed. The authors propose a service model for healthcare provision.